Clinical application of MOSkin dosimeters to rectal wall in vivo doismetry in gynecological and prostate HDR brachytherapy. (September 2016) - Carrara, M.; Mazzeo, D.; Romanyukha, A.; Tenconi, C.; Cerrotta, A.; Borroni, M.; Cutajar, D.; Petasecca, M.; Lerch, M.; Bucci, J.; Fallai, C.; Gambarini, G.; et al.
Abstract : Introduction: MO Skins are MOSFET dosimeters designed and developed at the Centre for Medical Radiation Physics (University of Wollongong, Australia), optimized to measure the dose in steep dose gradients. In this work, their clinical application to rectal wall in vivo dosimetry (IVD) during gynecological and prostate high dose rate brachytherapy (HDR-BT) was studied. Purpose: To evaluate the discrepancies between planned and measured doses to the rectal wall and to investigate the impact of the duration of the treatment planning procedure on these discrepancies. Materials and methods: In gynecological HDR-BT, three MO Skins were assembled over a semi-flexible rectal probe and 51 IVD measurements were performed. In prostate HDR-BT, two MO Skins were assembled on the trans-rectal ultrasound probe and 36 IVD measurements were performed. The absolute differences ΔD between measured and calculated doses in the estimated dosimeters positions were quantified and a possible correlation with the treatment planning time was investigated. Results: Grouping ΔD according to the time elapsed between imaging and treatment (i.e., group 1: ⩽90 min; group 2: >90 min), average ΔD for groups 1 and 2 were 5.1 ± 3.0% and 8.3 ± 6.2% for prostate and 3.8 ± 3.5% and 6.5 ± 4.3% for gynecology HDR-BT, respectively. Average ΔD were in both cases lower for group 1, demonstrating higher uncertainties of the calculated dose with higher treatment planning times (i.e., probability of morphological changes increases with time). Conclusion: MO Skin dosimeters coupled to rectal probes may be used for rectal IVD during gynecological/prostate HDR-BT. Planning time should be kept as low as possible to reduce uncertainties in calculated doses. Disclosure: none